Target system for the CC-series сyclotrons designed and manufactured in NIIEFA - Abramov, E.N.; Gavrish, Yu.N.; Gnutov, P.A.; Klopenkov, M.L.; Klopenkov, R.М.; Kravchuck, K.A.; Kuzhlev, A.N.; Melnikov, A.A.; Mudrolyubov, V.G.; Muraviev, G.V.; Strokach, A.P.; Zabrodin, B.V.; et al. (Вопросы атомной науки и техники, 2013)
A prototype of the target system for the CC-series cyclotrons for production of PET radionuclides C-11 and F-18 has been designed, manufactured and tested in the Efremov Institute. The target system will produce radionuclides sufficient to ensure the needs of a standard PET-center.